Antidiabetic activity of Centella asiatica (L.) urbana in alloxan induced Type 1 diabetic model rats - Rahman, Sonia; Jamal, MAH Mostofa; Parvin, Anzana; Mahfuz-Al-Mamun, Md; Islam, M Rezuanul (Journal of Bio-Science, 2012)
Context: Diabetes mellitus is becoming a major burden upon healthcare facilities in all affected countries. Current therapies used for diabetics have side effects, so the current shift to the use of herbal preparations may be more effective, relatively low cost, less side effect and low toxicity. Objective: The present research was made to investigate the potential antidiabetic activity of Centella asiatica (L.) Urb. in alloxen induced diabetics. Materials and Methods: Rats were divided into 6 groups and C. asiatica was administered containing 50, 100 and 200 mg/kgbwt powder, respectively in 1ml water orally in group A, B and C rats. Metformin (150 mg/kgbwt) used as a reference standard drug. Blood glucose (BG), triglycerides (TG), total cholesterol (TC), high density lipoproteins (HDL), low density lipoproteins (LDL), serum glutamate oxaloacetate transaminase (SGOT) and serum glutamate pyruvate transaminase (SGPT) were estimated from the serum by using standard kits. Results: C. asiatica juice had shown significant lowered the blood glucose levels in all groups. In addition, body weight, organ (liver, kidney, heart and pancreas) weight, food intake, water intake were also examined in all treated groups and compared against diabetic control group. After 22 days daily administration of C. asiatica, diabetic treated rats showed improvement in body weight, water intake as compared to diabetic control rats. In alloxan induced diabetic rats the maximum reduction in BG, TG, TC, HDL, LDL, SGOT and SGPT were observed at a dose level of 50 mg/kgbwt. Conclusion: The present data indicates that C. asiatica juice possesses potential as an antidiabetic action. DOI: http://dx.doi.org/10.3329/jbs.v19i0.12996 J. bio-sci. 19: 23-27, 2011